Method for in-situ decomposition reinforcement of face-centered AlxCoCr high-entropy alloy cladding layer

The AlxCrCoFeNi high-entropy alloy cladding is strengthened by Cr2AlC in situ decomposition, which solves the cavitation and corrosion problems of high-entropy alloy under high-speed liquid flow erosion, achieves the improvement of high-strength and corrosion resistance, and extends the turbine The service life of the blade.

CN119243144AActive Publication Date: 2025-01-03BEIJING JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411429059.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The AlxCrCoFeNi cladding of high-entropy alloy is prone to cavitation, rupture and corrosion problems under high-speed liquid flow erosion, resulting in damage to the surface of mechanical parts and reduced operating efficiency. The interface bonding force between traditional binary ceramics and high-entropy alloys is weak, making it difficult to Effectively strengthen the cladding.

Method used

Cr2AlC is used to produce nanoceramic particles in situ, and the MAX phase is formed at high temperature through laser cladding technology to ensure that AlxCrCoFeNi maintains the FCC single-phase structure, and CrCx is introduced as the reinforced phase to improve the hardness and corrosion resistance of the cladding layer.

Benefits of technology

A high-entropy alloy cladding layer with high strength, cavitation and corrosion resistance under low cost and simple processes has been achieved, extending the service life of the turbine blades and improving operating efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243144A_ABST
    Figure CN119243144A_ABST
Patent Text Reader

Abstract

The invention relates to a method for in-situ decomposition strengthening of a face-centered AlxCoCr high-entropy alloy cladding layer. The method is characterized in that a cladding layer comprises the following phase components in percentage by mass: 0-3% of Cr2AlC, 5-14.5% of CrCx and the balance of AlxCrCoFeNi with a face-centered cubic structure, and the cladding layer raw material powder comprises the following components in percentage by mass: 5-17.5% of Cr2AlC and the balance of AlxCrCoFeNi high-entropy powder. Cr2AlC is spherical or irregular, and the particle size of the Cr2AlC is 15-60 microns; alxCrCoFeNi is spherical, and the particle size of the AlxCrCoFeNi is 45-150 microns. The preparation method of the cladding layer comprises the following steps: putting the raw material powder into a three-dimensional rotary mixer, and fully and uniformly mixing; alloy steel serves as a base body, and rust removal and preheating are conducted; and the mixed powder is dried and then placed in a powder feeder of laser cladding equipment, and a cladding layer is prepared through laser cladding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the field of high entropy alloy cladding layer structure design, specifically an in-situ decomposition strengthening face-centered Al x A method for cladding a CoCr-based high entropy alloy layer. Background technology:

[0002] As a clean, high-quality renewable energy source, hydropower has rich development potential and huge commercial value.

[0003] As important components of hydropower units, flow-through parts such as turbine blades and runners are easily cavitated by high-speed and high-throughput liquid flow on their surfaces at locations such as the blade edges. The cavitation bubbles generated on the blade surface will cause high-frequency vibrations on the surface of mechanical parts, generate noise, and affect the stability of the mechanical system. The large amount of energy released by the bubble rupture will impact the surface of the contact parts, causing cavitation damage such as pinholes and fish-scale peeling on the surface of mechanical parts, seriously affecting their service life. The damage to the surface shape will also affect the flow conditions of the liquid flow, greatly affecting the operating efficiency of the turbine. At the same time, the scouring and abrasion of the surface of the turbine by the sediment in the liquid flow will further accelerate the failure rate of the surface of the parts. Therefore, strengthening the surface and extending its service life are the key to building long-life, high-stability, high-head and large-capacity hydropower stations in the future.

[0004] High entropy alloy cladding layers prepared by laser cladding technology have been widely researched and applied due to their excellent performance. Due to the synergistic effect of various elements in high entropy alloys, this type of material exhibits strength and toughness superior to traditional alloy materials, while also having excellent properties such as corrosion resistance and cavitation resistance. x CrCoFeNi series high entropy alloys have low cost and relatively simple preparation process. They have high strength, high toughness and corrosion resistance, and are ideal raw materials for preparing high entropy alloy cladding layers. Among the elements in this type of high entropy alloy, the Al content mainly affects the phase composition of the high entropy alloy. Only when x < 0.4, Al x CrCoFeNi high entropy alloy will form a high plasticity FCC single phase composition; when x>0.4, a multiphase structure composed of FCC, BCC and B2 phases will appear in the high entropy alloy. The complex phase composition will make it difficult to ensure the uniformity of the cladding layer during the preparation process, and the performance of the cladding layer will be unstable. In view of this, it is necessary to use ceramic particles to clad the FCC single phase Al x CrCoFeNi high entropy cladding layer is strengthened to improve the hardness and strength of the cladding layer. However, traditional binary ceramics, such as Al2O3, ZnO2, etc., are x The interface bonding strength of CrCoFeNi is weak, which can easily become the source of cracks in actual service, causing Al xCrCoFeNi high entropy cladding layer fails. Therefore, it is necessary to x Based on the face-centered cubic structure of CrCoFeNi, the ceramic reinforcement and Al x CrCoFeNi forms a strong interface bond.

[0005] The new ternary layered MAX phase ceramics are different from traditional binary ceramics. Under the high temperature of laser cladding, the A-site elements in the MAX phase will spontaneously diffuse outward and form a nano-ceramic reinforcement phase in situ. Therefore, this type of ceramic particles can play the role of solid solution strengthening and nano-particle strengthening at the same time. For example: the Al element diffusion and Al x CrCoFeNi forms a strong bonding interface and in situ forms nano-CrC x Improve the hardness and strength of the cladding layer. x The phase composition of CrCoFeNi is designed to strengthen the face-centered cubic structure of Al x CoCrFeNi high entropy alloy cladding method to ensure Al in the cladding layer x CrCoFeNi still maintains the FCC single-phase structure, while introducing MAX phase and ceramic particles produced by in-situ decomposition as strengthening phases becomes the research and development focus of this patent. Summary of the invention:

[0006] The object of the present invention is to provide an in-situ decomposition-strengthened face-centered cubic structure Al x Method for cladding CoCrFeNi high entropy alloy layer.

[0007] The in-situ decomposition-strengthened face-centered cubic structure Al x The design principles of the raw material composite powder composition of the CoCrFeNi high entropy alloy cladding layer are as follows:

[0008] The Al element produced by the in-situ decomposition of Cr2AlC enters the Al x After the CrCoFeNi grains are formed, x≤0.4 to ensure its FCC single-phase structure. 0.3 Taking CrCoFeNi as an example, after adding Cr2AlC, due to its full decomposition during the preparation of the composite cladding layer, the Al element diffuses into the high entropy alloy. Assuming that the Al element completely enters the high entropy alloy, it can be calculated that the mass fraction of Cr2AlC cannot exceed 7.84%. Considering the burnout of the low melting point element Al during the preparation of the cladding layer, its mass fraction can be relaxed to 12%, that is, for Al 0.3 The maximum limit mass fraction of CrCoFeNi and Cr2AlC is 12%.

[0009] It should be noted that for Al with x < 0.4 x CrCoFeNi can design the Cr2AlC content according to the above design principles to meet the Al content in the cladding layer. x CrCoFeNi maintains the single-phase structure of FCC.

[0010] The in-situ decomposition-strengthened face-centered cubic structure Al x The composition of raw material powder for preparing CoCrFeNi cladding layer is as follows:

[0011] According to the design principle of the composite powder of the present invention, the mass percentage of the raw material powder of the cladding layer of the present invention is: Cr2AlC: 5-17.5%, and the rest is Al x CrCoFeNi high entropy alloy powder, the sum of the mass fractions of the two is 100%. In addition, the shape and particle size of the raw material powder of the cladding layer meet the following definitions: Cr2AlC: spherical or irregular shape, particle size 15-60μm; Al x CrCoFeNi: spherical, particle size 45-150μm.

[0012] The in-situ decomposition-strengthened face-centered cubic structure Al x The final composition of the CoCrFeNi cladding layer is as follows:

[0013] The present invention in-situ decomposition strengthening face-centered cubic structure Al x The CoCrFeNi cladding layer is characterized by the phase composition and mass fraction of each phase in the cladding layer: Cr2AlC: 0-3%; CrC x : 5-14.5%; the rest is Al x CrCoFeNi. At the same time, Al in the cladding layer x CrCoFeNi is a single phase FCC. The sum of the mass fractions of each component is 100%.

[0014] The in-situ decomposition-strengthened face-centered cubic structure Al x The properties of CoCrFeNi cladding layer are as follows:

[0015] The porosity of the composite cladding layer is less than 3%, its thickness is 0.5-2.5mm, and the surface hardness of the composite cladding layer is 600-700HV 0.2 The cavitation resistance of the composite cladding layer is tested according to the ASTM G32-6 material cavitation resistance test standard, and the volume loss rate is less than 0.5mm 3 / h, the erosion resistance of the composite cladding layer was tested according to the ASTM G76-2018 material erosion performance test standard, and its mass loss rate was less than 10mg / min.

[0016] The in-situ decomposition-strengthened face-centered cubic structure Al x The preparation method of CoCrFeNi cladding layer is as follows:

[0017] Step 1: According to the composite powder design principle, Al x CrCoFeNi and Cr2AlC are placed in a three-dimensional rotary mixer and mixed thoroughly to obtain composite raw material powder;

[0018] Step 2, using alloy steel as the cladding layer to prepare a substrate, cleaning and derusting its surface, preheating it to 180° C. in an insulated box, keeping it warm for 3-5 minutes, and then fixing it on a fixture;

[0019] Step 3: After drying the composite powder, place it in the powder feeder of the laser cladding equipment, and perform laser cladding on the alloy steel substrate to prepare Cr2AlC reinforced face-centered cubic structure Al x CrCoFeNi (x≤0.4) high entropy alloy cladding layer, the specific preparation parameters are as follows: laser power 1000-1200W, scanning speed 400-800mm / min, spot diameter 3-4mm, powder feeding rate 15-20g / min, overlap rate 40-50%, defocusing amount +3mm;

[0020] Step 4, the thickness of the cladding layer finally obtained is 0.5-2.5 mm; the phase composition and mass fraction of each phase in the cladding layer are: Cr2AlC: 0-3%; CrC x : 5-14.5%, the rest is Al x CrCoFeNi; Al in cladding layer x CrCoFeNi is a single phase FCC. The sum of the mass fractions of each component is 100%.

[0021] Compared with the prior art, the present invention has the following technical advantages:

[0022] The present invention provides an in-situ decomposition-strengthened face-centered cubic structure Al x The CoCrFeNi cladding method has obvious advantages in improving the cavitation and erosion resistance of turbine blades and turbine blades. The powder used is simple to obtain and has low cost. x On the basis of CrCoFeNi, low-cost micron-level powder is used to in-situ generate nano-level ceramic reinforcement phase to further improve the cavitation and erosion resistance of the cladding layer. The preparation process of the cladding layer is simple and highly repeatable, with practical application prospects and considerable economic benefits. Description of the drawings:

[0023] Figure 1 It is the 5wt.%Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3Cross-sectional morphology of CoCrFeNi cladding layer

[0024] Figure 2 It is the 9wt.%Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3 Cross-sectional morphology of CoCrFeNi cladding layer

[0025] Figure 3 The 12wt.% Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3 Cross-sectional morphology of CoCrFeNi cladding layer Specific implementation method:

[0026] Example 1

[0027] According to the mass percentage of the raw material powder of the cladding layer: Cr2AlC: 5%, Al 0.3 CrCoFeNi 95%, the sum of the two components is 100%, weigh the required powder; place the above two raw material powders in a three-dimensional rotary mixer and mix them evenly; use alloy steel as a cladding layer to prepare a substrate, clean and derust its surface, preheat it to 180°C in an insulation box, keep it warm for 3-5 minutes and then fix it on a fixture; dry the mixed powder for 30 minutes and place it in a powder feeder of a laser cladding equipment, and perform laser cladding on the alloy steel substrate according to the process described in the claim to prepare Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3 CoCrFeNi cladding layer. The final composite cladding layer is as shown in the attached Figure 1 shown.

[0028] Example 2

[0029] According to the mass percentage of raw material powder of composite cladding layer: Cr2AlC: 9%, Al 0.3 CrCoFeNi 93%, the sum of the two components is 100%, weigh the required powder; place the above two raw material powders in a three-dimensional rotary mixer and mix them evenly; use alloy steel as a cladding layer to prepare a substrate, clean and derust its surface, preheat it to 180°C in an insulation box, keep it warm for 3-5 minutes and then fix it on a fixture; dry the mixed powder for 30 minutes and place it in a powder feeder of a laser cladding equipment, and perform laser cladding on the alloy steel substrate according to the process described in the claim to prepare Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3 CoCrFeNi cladding layer. The final cladding layer is as shown in the attached Figure 2 shown.

[0030] Example 3

[0031] According to the mass percentage of raw material powder of composite cladding layer: Cr2AlC: 12%, Al0.3 CrCoFeNi 91%, the sum of the two components is 100%, weigh the required powder; place the above two raw material powders in a three-dimensional rotary mixer and mix them evenly; use alloy steel as a cladding layer to prepare a substrate, clean and derust its surface, preheat it to 180°C in an insulation box, keep it warm for 3-5 minutes and then fix it on a fixture; dry the mixed powder for 30 minutes and place it in a powder feeder of a laser cladding equipment, and perform laser cladding on the alloy steel substrate according to the process described in the claim to prepare Cr2AlC in-situ decomposition strengthening face-centered cubic structure Al 0.3 CoCrFeNi cladding layer. The final cladding layer is as shown in the attached Figure 3 shown.

Claims

1. An in-situ decomposition strengthened face-centered Al x The method for cladding a CoCr-based high entropy alloy layer is characterized in that: The method comprises the following steps: Step 1: Al x CrCoFeNi powder and Cr2AlC powder are placed in a three-dimensional rotary mixer and mixed thoroughly to obtain composite raw material powder; Step 2, using alloy steel as a coating to prepare a substrate, cleaning and derusting its surface, preheating it to 180° C. in an insulated box, keeping it warm for 3-5 minutes, and then fixing it on a fixture; Step 3: After drying the composite powder, place it in the powder feeder of the laser cladding equipment, and perform laser cladding on the alloy steel substrate to prepare Cr2AlC reinforced face-centered cubic structure Al x CrCoFeNi high entropy alloy coating, the specific preparation parameters are as follows: laser power 1000-1200W, scanning speed 400-800mm / min, spot diameter 3-4mm, powder feeding rate 15-20g / min, overlap rate 40-50%, defocusing amount +3mm; Step 4: The final composite coating thickness is 0.5-2.5 mm, Cr2AlC: 0-3%; CrC x : 5-14.5%; the rest is Al x CrCoFeNi, the Al formed x CrCoFeNi is a single-phase FCC, and the sum of the mass fractions of each component is 100%.

2. The in-situ decomposition-strengthened face-centered cubic structure Al according to claim 1 x CrCoFeNi high entropy cladding layer, characterized in that: The mass percentage of raw material powder used to prepare the composite coating is: Cr2AlC: 5-17.5%, the rest is Al x CrCoFeNi high entropy alloy powder, the sum of the mass fractions of the two is 100%; in addition, the shape and particle size of the composite coating raw material powder meet the following definitions: Cr2AlC: spherical or irregular shape, particle size 15-60μm; Al x CrCoFeNi: spherical, particle size 45-150μm.

3. The in-situ decomposition-strengthened face-centered cubic structure Al according to claim 1 x The method for forming a CrCoFeNi high entropy cladding layer is characterized in that: There is a limit to the amount of Cr2AlC added. The Al element in the raw material powder is converted to Al x CrCoFeNi satisfies x≤0.

4.

4. The in-situ decomposition-strengthened face-centered cubic structure Al according to claim 1 x The method for CrCoFeNi high entropy cladding layer, the prepared composite coating has a porosity of less than 3%, a thickness of 0.5-2.5mm, and a surface hardness of 600-700HV 0.2 The cavitation resistance of the composite coating was tested according to the ASTM G32-6 material cavitation resistance test standard, and the volume loss rate was less than 0.5mm 3 / h, the erosion resistance of the composite coating was tested according to ASTM G76-2018 material erosion performance test standard, and its mass loss rate was less than 10mg / min.

5. The in-situ decomposition-strengthened face-centered cubic structure Al according to claim 1 x Al2O3 prepared by CrCoFeNi high entropy cladding method x CrCoFeNi composite coating, characterized in that: The chemical composition mass percentage of the composite coating is: Cr2AlC: 0-3%, CrC x : 5-17.5%, the rest is Al x CrCoFeNi, the Al formed x CrCoFeNi is a single-phase FCC, and the sum of the mass fractions of each component is 100%.

Citation Information

Patent Citations

  • Application of high-entropy alloy powder in laser cladding

    CN115852357A

  • Ceramic particle reinforced eutectic high-entropy alloy wear-resistant coating and preparation method thereof

    CN118186386A

  • High-entropy surface coating for protecting metal downhole

    US20240123706A1

  • Single phase high entropy intermetallics and method for manufacturing

    WO2022099092A1